Distribusi Kekayaan Dalam Islam (Telaah Terhadap Pemikiran Ibnu Abī Al-Dunyā Dalam Kitab Iṣlāh al-Māl) - Abdul Ghofar Saifudin (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2020)
Islam is the religion conducting all aspects of life and allowing followers to gain wealth. This recognition draws on private property. Through private property, they are ordered to distribute it to the poverty class. The research aims to examine the idea of a classic figure Ibn Abī al-Dunyā, who spoke about the private property, the distribution, and the relevance to the present context. The research type applies a descriptive qualitative approach to socio-historical philosophical. This study uses primary based on the works of Ibn Abī al-Dunyā and secondary sources such as books, journals, and papers relating to the topics. Techniques offered by analysis in this paper uses a domain model and taxonomy. The research concludes that wealth based on Ibn Abī al-Dunyā is a give of Allah Swt. However, a part of that should be distributed to the appropriate persons. He convinces that wealth comes from two ways: directly (work) and indirect (hire). Then the distribution of wealth not limited to post-acquisition but also on the process assemble it. Distribution justice may be reached if the monopoly and hoarding method do not exist.